2015
DOI: 10.1093/icvts/ivv091
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan tubes can restore the function of resected phrenic nerves

Abstract: Our results suggest that, in addition to morphological improvement, C-tube implantation can functionally improve the injured phrenic nerve by promoting phrenic nerve regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…A chitosan hollow tube employed for regeneration of the injured rodent transected sciatic nerve yielded results comparable to autologous nerve graft repair [ 83 ]. Implantation of chitosan nanofiber tube could partially restore the function of a damaged phrenic nerve in beagle dogs as seen in improvement of diaphragm movement, slow phrenic nerve conduction, connection of the damaged nerve by newly regenerating nerve fibers surrounded by granulation tissue within the chitosan nanofiber tube [ 84 ]. The loss of spinal cord tissue and cavity formation impedes the repair of damage to the spinal cord.…”
Section: Applicationsmentioning
confidence: 99%
“…A chitosan hollow tube employed for regeneration of the injured rodent transected sciatic nerve yielded results comparable to autologous nerve graft repair [ 83 ]. Implantation of chitosan nanofiber tube could partially restore the function of a damaged phrenic nerve in beagle dogs as seen in improvement of diaphragm movement, slow phrenic nerve conduction, connection of the damaged nerve by newly regenerating nerve fibers surrounded by granulation tissue within the chitosan nanofiber tube [ 84 ]. The loss of spinal cord tissue and cavity formation impedes the repair of damage to the spinal cord.…”
Section: Applicationsmentioning
confidence: 99%
“…It was confirmed that the C-tube can be safely and effectively applied in the recovery and regeneration of the damaged phrenic and sympathetic nerves [144]. Tanaka et al conducted similar experiments following Matsumoto's process and reached the same conclusion [145]. Yu et al prepared MC with a chitosan amine group as material, and then formed scaffolds by radical polymerization and cross-linking.…”
Section: Nervous Systemmentioning
confidence: 85%
“…Chitosan-based nerve conduits, alone or in combination with other biomaterials, have been found to bridge efficiently peripheral nerve defects (Gnavi et al 2013). Apart from rats (Gonzalez-Perez et al 2015;Fregnan et al 2016), chitosan conduits have been tested in several animal models for nerve regeneration, such as dogs (Tanaka et al 2015) and goats (Muheremu et al 2017). To provide an example, chitosan nerve conduits having an internal longitudinal chitosan membrane were used on a 10-mm sciatic nerve defects in adult healthy and diabetic rats and provide an enhancement in functional and morphological nerve regeneration (Meyer et al 2016).…”
Section: Chitosan As a Promising Materials For Regenerative Medicinementioning
confidence: 99%